2015
DOI: 10.1021/acsnano.5b04879
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Strategy for Fabricating Connected Graphene Nanoribbons

Abstract: We use self-assembly to fabricate and to connect precise graphene nanoribbons end to end. Combining scanning tunneling microscopy, Raman spectroscopy, and density functional theory, we characterize the chemical and electronic aspects of the interconnections between ribbons. We demonstrate how the substrate effects of our self-assembly can be exploited to fabricate graphene structures connected to desired electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 50 publications
9
105
0
Order By: Relevance
“…For example, consider the scheme for fabrication of graphene nanoribbons shown in Figure 1. [12][13][14][15] In this scheme, 10,10'-dibromo-9,9'-bianthracene (Br 2 BA) molecules are deposited onto a copper(111) (Cu(111)) surface ( Figure 1A), which then undergo a self-assembly process to form chain-shaped structures ( Figure 1B). Upon heating, a chemical reaction occurs and the chains transform into (3,1)-chiral edge graphene nanoribbons ( Figure 1C).…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, consider the scheme for fabrication of graphene nanoribbons shown in Figure 1. [12][13][14][15] In this scheme, 10,10'-dibromo-9,9'-bianthracene (Br 2 BA) molecules are deposited onto a copper(111) (Cu(111)) surface ( Figure 1A), which then undergo a self-assembly process to form chain-shaped structures ( Figure 1B). Upon heating, a chemical reaction occurs and the chains transform into (3,1)-chiral edge graphene nanoribbons ( Figure 1C).…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…While the mechanism of this chemical reaction has not been rigorously determined, it is believed to involve a cyclodehydrogenation reaction. 13 However, in order for such a 'classical' chemical reaction to actually occur, the frontier orbitals of the Br 2 BA molecules in the chain must be relatively well defined, despite the expected strong hybridization of the frontier orbitals with the metal surface bands. For the case of van der Waals-adsorbed organic molecules, a Author to whom correspondence should be addressed.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…In the study performed by Han et al, self-assembly fabricated GNRs were connected end to end. 19 Surface-assisted molecular assembly (SAMA) was used to synthesize and connect GNRs end to end both chemically and electronically. It was also mentioned that the Cu(111) substrate plays an important role for the molecules to form and connect the GNRs up to 50 nm long.…”
Section: A Synthesis and Fabrication Techniquesmentioning
confidence: 99%
“…Additionally, it has been reported that the GNRs could be interchain-linked via cross-dehydrogenative coupling. 26,27 These phenomena will be applicable to produce the covalently bonded π-conjugated 2D structures. However, the linked GNRs reported thus far have low density resulting in the undeveloped 2D structures.…”
mentioning
confidence: 99%
“…These results are in good agreement with previously reported chiral GNR. 26 In summary, high-density interchain-linked GNRs from precursor 1,9-dibromodibenzo[g,p]chrysene were fabricated via 2Z-CVD. The fabrication process consists of polymerization, intramolecular-and intermolecular dehydrogenation.…”
mentioning
confidence: 99%